1979
DOI: 10.1016/0005-2736(79)90316-x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of lysophosphatidylcholine in bovine chromaffin granules

Abstract: SummaryOne of the unique features of the chromaffin granule membrane is the presence of about 17 mol% lysophosphatidylcholine. Lysophosphatidylcholine isolated from the granules could be degraded by approx. 94% by lysophospholipase. This result is consistent with chemical analyses data showing that about 9% of this lysophospholipid is l'-alkenyl glycerophosphocholine.The localization of the acylglycerophosphocholine in the chromaffin granule membrane was studied by using pure bovine liver lysophospholipases. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Total lipids were extracted (Bligh & Dyer, 1959) from the large granule fraction, and the phospholipid composition was obtained by two-dimensional TLC followed by visualization by iodine vapor and assay of phospholipid phosphorus in the various spots. The composition on a mole percent basis was found to be 8.1% phosphatidylserine, 10.1% lysophosphatidylcholine, 15.1% sphingomyelin, 35.7% phosphatidylethanolamine, and 31% phosphatidylcholine, consistent with literature values (de Oliveira-Filgueiras et al, 1979).…”
Section: Methodssupporting
confidence: 88%
“…Total lipids were extracted (Bligh & Dyer, 1959) from the large granule fraction, and the phospholipid composition was obtained by two-dimensional TLC followed by visualization by iodine vapor and assay of phospholipid phosphorus in the various spots. The composition on a mole percent basis was found to be 8.1% phosphatidylserine, 10.1% lysophosphatidylcholine, 15.1% sphingomyelin, 35.7% phosphatidylethanolamine, and 31% phosphatidylcholine, consistent with literature values (de Oliveira-Filgueiras et al, 1979).…”
Section: Methodssupporting
confidence: 88%
“…For example, equimolar mixtures of LPC and fatty acids form bilayers, based on which the retardation of haemolysis by such mixtures could be explained. 4a Viability of certain cell types and organelles in the presence of significant concentrations of LPC 16 was attributed to bilayer formation between fatty acid and LPC. 4a Equimolar mixtures of LPC and cholesterol also form a complex and it has been suggested that cholesterol can buffer the membranolytic effect of LPC.…”
mentioning
confidence: 99%